Pembelajaran Moderasi Beragama dalam Pembentukan Sikap Anti Kekerasan di MTsN 1 Jombang - Burhanuddin, Muhammad; Ashoumi, Hilyah (Universitas KH. A. Wahab Hasbullah, 2023)
The purpose of this study was to determine the teacher's efforts in instilling religious moderation learning in the formation of anti-violence attitudes at MTsN 1 Jombang. This research is descriptive using a qualitative approach, the researcher is the key instrument, data collection techniques are triangulated (combined), data analysis is inductive and research results emphasize meaning rather than generalization. The cultivation of Religious Moderation Learning in the Formation of Anti-Violence Attitudes at MTsN 1 Jombang through subject handbooks which are then developed or elaborated through interactive learning media. Although there are also teachers who utilize the surrounding circumstances or conditions as well as dark events that have occurred in Indonesia that can be learned from the values of religious moderation contained therein.